The Effect of Palm Sap Substitution on Sandwich Bread Characteristics - Durrotul Asyfiya Khusnayati; Chandra, Teddy; Sufianti, R. Arti (Politeknik Pariwisata NHI Bandung, 2024)
Purpose of the study: This research was conducted to investigate the potential of palm sap locally known as legen water as a substitute for instant yeast, commonly used as a leavening agent in sandwich bread production. Design/methodology: The research employed an experimental method. A hedonic test utilizing a 9-point likeness scale was administered to panelists through questionnaires. The palm sap used in this study was 3-4 hours old and collected during the evening tapping session. Findings: Legen water tapped from the siwalan tree (Borassus flabellifer) during afternoon tapping can replace the role of instant yeast and affect the color, taste, texture, and aroma of sandwich bread products and also provide its own characteristics to the product. Research limitations/Implication: The results of this research will be useful for traditional bread entrepreneurs because the instant yeast that is usually used can be replaced with legen water which is widely available in East Java region. Novelty/Originality of the study: This research contributes to the understanding of alternative leavening agents in bread production and explores the potential applications of palm sap in food technology.